Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

the solution set of 4x-(x+7)=2(x+3)​

Sagot :

Step-by-step explanation:

  • 4x-(x+7)=2(x+3)
  • 4x-x-7=2x+6
  • 3x-2x=6+7
  • x=13

hope it helps.

Answer:

x=13

Step-by-step explanation:

4x-(x+7)=2(x+3)

change the sign of (x+7) as it has minus before the bracket and multiply 2 with (x+3)

4x-x-7=2x+6

Now bring all variables to one sides and the non to the other

4x-x-2x=6+7

Simplify

x=13

Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.